2021
DOI: 10.1002/jmor.21327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of collagen distribution in the dermis of the embryonic carapace of soft‐ and hard‐shelled cryptodiran turtles

Abstract: Turtles are characterized by their typical carapace, which is primarily composed of corneous beta proteins in the horny part and collagen in the dermal part. The formation of the extracellular matrix in the dermis of the carapace in a hard‐shelled and a soft‐shelled turtle has been compared. The study examines carapace development, with an emphasis on collagen accumulation, in the soft‐shelled turtle Pelodiscus sinensis and hard‐shelled turtle Trachemys scripta elegans, using comparative morphological and embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, these cuticular protein genes had covered almost all the cuticular protein families of RR-1, RR-2, Tweedle, CPFL, CPG, and CPH, with the exception of RR-3 [ 25 ]. Intriguingly, another group of molecular structure such as collagens were all down-regulated in mutation of BmMETTL4 ( Figure 7 C), whereas collagenase responsible for degrading native collagen were significantly up-regulated ( Figure 7 D) [ 26 , 27 ]. These analyses indicated important roles of structural proteins in the process of embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these cuticular protein genes had covered almost all the cuticular protein families of RR-1, RR-2, Tweedle, CPFL, CPG, and CPH, with the exception of RR-3 [ 25 ]. Intriguingly, another group of molecular structure such as collagens were all down-regulated in mutation of BmMETTL4 ( Figure 7 C), whereas collagenase responsible for degrading native collagen were significantly up-regulated ( Figure 7 D) [ 26 , 27 ]. These analyses indicated important roles of structural proteins in the process of embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that there were many DEGs possessing molecular structure activity, including structural molecular proteins in the extracellular matrix (ECM)-interaction pathway such as collagens, that were all generally down-regulated in BmMETTL4 mutant. Collagen can provide structural support for cell growth and proliferation, help maintain the structural integrity of the body and organs, and play a crucial role during embryonic tissue morphogenesis [ 26 ]. In silkworm, we identified 17 collagens belonging to different collagen types in the genome, of which 7 collagens were significantly repressed by depletion of BmMETTL4.…”
Section: Discussionmentioning
confidence: 99%
“…The content of hydroxyproline was quantified using acid hydrolysis followed using a colorimetric method according to Reddy and Enwemeka (1996). The detailed procedure was described in Yang et al (2021).…”
Section: Collagen Content Determinationmentioning
confidence: 99%